2022
DOI: 10.1002/ejic.202101002
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Coordinate NHC‐Supported ZnIIOrganocations: Steric and Electronic Tunability and Use in Alkyne Hydroboration Catalysis

Abstract: Dedicated to Professor Rinaldo Poli on the occasion of his 65th birthday.We herein report on the synthesis, structure, and use in alkyneled to with robust and stable two-coordinate Zn II cations [(IPrCl)ZnÀ R] + (3 a, R=Et; 3 b, R=Me) and [(ItBu)ZnÀ Et] + (4), respectively, all isolated as [B(C 6 F 5 ) 4 ] À salts. Further derivatization of alkyl cations 3 b and 4 by reaction with one equivalent of [B(C 6 F 5 ) 3 ] afforded cations [(IPrCl)ZnÀ C 6 F 5 ] + (5) and [(ItBu)ZnÀ C 6 F 5 ] + (6) as [B(C 6 F 5 ) 4 ] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…BF 4 − or SbF 6 − ). However, the shortest Zn⋯F–C were found in four ionic complexes with organic fluorinated anions, 30 with the hitherto closest approach, 2.471 Å, corresponding to the interaction of a linear cation [(NHC)Zn(C 6 F 5 )] + with [B(C 6 F 5 ) 4 ] − as its counteranion. 30 a Most of the remaining Zn⋯F–C contacts (192 = 86%) fall within the range of 2.7–3.0 Å.…”
Section: Resultsmentioning
confidence: 97%
“…BF 4 − or SbF 6 − ). However, the shortest Zn⋯F–C were found in four ionic complexes with organic fluorinated anions, 30 with the hitherto closest approach, 2.471 Å, corresponding to the interaction of a linear cation [(NHC)Zn(C 6 F 5 )] + with [B(C 6 F 5 ) 4 ] − as its counteranion. 30 a Most of the remaining Zn⋯F–C contacts (192 = 86%) fall within the range of 2.7–3.0 Å.…”
Section: Resultsmentioning
confidence: 97%
“…30,31 Since Nikonov and coworkers discovered that a Mo(IV) complex could catalyse the hydroboration of nitriles in 2012, 32,33 research on the hydroboration of nitriles or alkynes has been increasing. A plethora of transition-metal complexes, such as zirconium, 34 manganese, 35 iron, 36,37 cobalt, 22,[38][39][40][41][42][43] nickel, [44][45][46] zinc, [47][48][49][50][51][52][53] ruthenium, [54][55][56] palladium, 57 and many rare-earth metal complexes, [58][59][60] can catalyse the hydroboration of nitriles or alkynes. In recent years, earth-abundant, nontoxic and inexpensive main group-metal compounds have become favourable catalysts in these research fields.…”
Section: Introductionmentioning
confidence: 99%
“…Recently zinc complexes have also started to gain the attention of researchers as potential catalysts for hydroboration reactions. [33][34][35][36][37][38][39] Yao et al and Mukherjee et al independently reported multidentate phenolate ligand-supported zinc alkyl complexes and N-heterocyclic carbine-based zinc complexes as catalysts for regioselective hydroboration of N-heteroarenes. 40,41 The Nembenna group established a conjugated bis-guanidinate zinc hydride complex as a catalyst for the hydroboration of isonitriles, nitriles and esters.…”
Section: Introductionmentioning
confidence: 99%